Women in the Boardrooms of FTSE 250 Companies and Their Impact on Firm Performance - Kingham, Ashley (2015)
The purpose of this study was to examine whether there is a relationship between the amount of female directors on the boards of FTSE 250 companies and the observed companies’ performance. Previous researchers have had mixed results and differing opinions on the effects of this relationship, with papers finding positive and negative relationships, there are also several notable papers finding no relationship at all between these two factors.